(untitled) - Vernon L Avila (Boston, Massachusetts, 1995)
The book is divided into 7 units. Beginning with Unit 1, an introduction to the basic concepts, controversies, and wonders of biology. Unit 2 explores the molecular machinery of the cell. Unit 3 discusses the concepts of genetics. Unit 4 ties the concepts of evolution to the genetics of the previous unit and introduces the diversity of living organisms. The chapter in Unit 5 (Plants) and Unit 6 (Animals) emphasize current research and relevant examples. The final unit, Behavior and Ecology, brings the text to a close by integrating the ideas of energy transduction and evolution in a discussion of an organism's interaction with its environment
Keywords: biology